MISINTERPRETATION OF SALAFI JIHADIST ON JIHĀD VERSES: AN ANALYSIS - Hudzaifah Achmad Qotadah; Maisyatusy Syarifah; Adang Darmawan Achmad (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2021)
Nowadays, the term